Sistem Informasi Inventarisasi Barang Pada SMA Negeri 12 Kota Jambi - Syaifudin, Syaifudin; Purnama, Benni (LPPM Universitas Dinamika Bangsa, 2024)
Information technology is also inseparable from the management process, this is because almost everymanagement decision always requires information technology support including one in assetmanagement, in the field of management, an asset management information system is offered with theaim of facilitating the management of the assets themselves so that they can be produce reliable, relevant,timely, tested and understandable information data. Inventory is a list of all the facilities in all sections.From the results of the analysis that the author did at SMA Negeri 12 Jambi City on the inventoryinformation system currently running, there are several problems that occur, such as frequent duplicationwhen collecting inventory data, difficulties in searching for item data because the data is not wellintegrated. So that it is easy for data loss to occur and the length of time for making the desired inventoryreport. This study aims to analyze and design an information system for inventorying goods at SMANegeri 12 Jambi City. The method used in this study is the waterfall method. The design of thisinformation system produces prototypes using the Unified Modeling Language programming language.The designed information system can simplify the process of inputting inventory data for SMA Negeri 12Kota Jambi.